ANALISIS BREAK EVEN POINT USAHA PUDING LAMOTA - Elisa Juniarti; Mia Maelani; Hasdita Elies Ramadani; Elliza Rizki Wandani; S Suprianto (Samalewa: Jurnal Riset & Kajian Manajemen, 2022)
One of the planning analyzes to increase profits which is later expected to be used in determining the selling price of a product is through break even point (BEP) analysis. Break even point analysis is very important for companies because it will allow companies to determine the level of operations that must be carried out so that all operating costs can be covered and break event point analysis is also used to evaluate certain sales levels in relation to profit levels. The results of the break even point analysis of the Lamota Pudding business show that the selling price per cup of Lamota Pudding is Rp. 5,000, the sales volume per month is 750 cups or Rp. 3,750,000, fixed costs per unit are Rp. 2,752, - and variable costs per unit. unit amounting to Rp.3.975, - then obtained Break Even Point Unit of 3 units per month, Break Even Point Rupiah per month amounting to Rp. 13,420,-. Therefore, Puding Lamota business is considered feasible because it is able to provide a very high contribution margin or profit contribution of Rp. 1,025,- per unit or 99.8 percent.